Biological Characteristics and Pathogenicity of Helcococcus ovis Isolated From Clinical Bovine Mastitis in a Chinese Dairy Herd - Liu, Kai; Deng, Zhaoju; Zhang, Limei; Gu, Xiaolong; Liu, Gang; Liu, Yang; Chen, Peng; Gao, Jian; Han, Bo; Qu, Weijie (Frontiers in Veterinary Science, 2022)
Abstract Helcococcus ovis (H. ovis) was first reported in ovine subclinical mastitis milk and post-mortem examinated organs in Spain and the United Kingdom in 1999, subsequently, it appeared in cattle, horse, goat, and human. However, isolation and characterization of the strain in clinical bovine mastitis is unknown. Therefore, our objective was to identify the pathogen in clinical bovine mastitis. A total of 4 strains from 34 bovine mastitis milk samples were identified, there are tiny and transparent colonies from clinical bovine mastitis milk samples in a Chinese dairy farm, however, these colonies could not be identified using on-farm biochemical tests. The isolates were transported to Mastitis Diagnostic Laboratory of China Agricultural University in Beijing. The colonies were identified as a mixture of H. ovis and Trueperella pyogenes according to microscopic examination and 16S rRNA gene sequencing and the phylogenetic tree was constructed using 16S rRNA gene sequence of H. ovis isolates. In addition, the growth curve and biochemistry test were performed, we also examined the antimicrobial resistance profiles and constructed murine mammary infection model. Our results showed that the H. ovis was closely related to the strains isolated from China and Japan, growth speed of H. ovis was relatively slower than S.agalactiae, the phenotypic characteristics were similar to H. ovis CCUG37441 and CCUG39041 except to lactose; isolates were sensitive to most of antimicrobials; H. ovis could lead to mild murine mastitis and induce severe mastitis when co-infected with Trueperella pyogenes. In this report, we described the characteristics and pathogenicity of H. ovis that are associated with clinical bovine mastitis in China for the first time.